Stability analysis of micropolar fluid flow over an exponentially permeable shrinking sheet - Yahaya, Rusya Iryanti; Md. Arifin, Norihan; Mohamed Isa, Siti Suzilliana Putri (Academy of Sciences Malaysia, 2020)
In the present paper, stability analysis is performed to the dual solutions obtained in boundary layer flow of micropolar fluid over a shrinking sheet with exponential velocity. The problem is first considered as time-dependent problem. Then, the governing equations are transformed into ordinary differential equations using similarity transformations. Linear eigenvalue equations are introduced, and the smallest eigenvalues are computed by using a MATLAB solver called the bvp4c solver. The first solution is found to have positive smallest eigenvalues, while the second solution has negative smallest eigenvalues. Thus, the stable solution is the first solution, while the second solution is unstable.